2022
DOI: 10.46490/bf599
|View full text |Cite
|
Sign up to set email alerts
|

Results of ethnoecological studies in the prospect of forest tourism development in Tenganan Pegringsingan traditional village, Karangasem, Bali

Abstract: This study mainly discusses the lack of implementation of forest development as a tourist attraction in Karangasem, Bali, Indonesia. This research aims to implement the results of ethnoecological studies to develop the Bukit Kangin Forest tourism in the traditional village of Tenganan Pegringsingan, Karangasem, Bali. The population in this study area is considered in two aspects, namely the ecosystem aspect and the socio-system one. The population of the ecosystem consists of all plant species in Bukit Kangin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Also, the distances from the natural forest and the scarcity of the NTFPs probably may be the major reasons for the harvesting of NTFPs from the sacred forest and the cultivation of these NTFPs in the home gardens. This study supports several studies [13,16,17] that demonstrate how vital it is for rural residents, especially the poor, to cultivate and collect NTFPs from home gardens as an alternative source of revenue and subsistence. Additional research [14,18,19] revealed that the products support a variety of livelihoods and serve as a safety net, especially when agricultural production is inadequate to mitigate risk and fill the food shortfall gap in various areas.…”
Section: Logistic Regression Analysis Obudusupporting
confidence: 90%
See 1 more Smart Citation
“…Also, the distances from the natural forest and the scarcity of the NTFPs probably may be the major reasons for the harvesting of NTFPs from the sacred forest and the cultivation of these NTFPs in the home gardens. This study supports several studies [13,16,17] that demonstrate how vital it is for rural residents, especially the poor, to cultivate and collect NTFPs from home gardens as an alternative source of revenue and subsistence. Additional research [14,18,19] revealed that the products support a variety of livelihoods and serve as a safety net, especially when agricultural production is inadequate to mitigate risk and fill the food shortfall gap in various areas.…”
Section: Logistic Regression Analysis Obudusupporting
confidence: 90%
“…LGA AIN = -12.06588 + 5.662x 1 + 3.96x 2 + 2.677x 3 + 6.136x 4 -10.134x 5 + 2.024x 6 -4.658x 7 + 4.3225x 8 -3.653x 9 (17) Odds ratio (unit change): constant (0.000); x 1 (261.446), x 2 (52.482), x 3 (14.536); x 4 (462.368); x 5 (0.000);x 6 (7.572); x 7 (0.009); x 8 (76.088), x 9 (38.755).…”
Section: Logistic Regression Analysis Obudumentioning
confidence: 99%